Avian species and functional diversity in the Yellow River Wetland Nature Reserve of Henan Province - Wanying Li; Kaiyue Wang; Peisen Yan; Tianen Chen; Haipeng Zhao; Xunling Lu (Global Ecology and Conservation)
This study focused on the Yellow River Wetland Nature Reserve of Henan Province, China. We calculated species and functional α diversity indices and decomposed β diversity into turnover and nestedness components to examine the species and functional diversity of bird communities across different seasons (breeding and wintering) and their ecological assembly processes. The results revealed: (1) The breeding season demonstrated higher species richness, whereas the wintering season exhibited significantly higher numbers of protected bird species compared to the breeding season. (2) The β diversity of species was predominantly driven by turnover components in both seasons, while functional β diversity was primarily influenced by nestedness components. The inconsistency between species and functional β diversity components suggested the presence of functional trait redundancy. (3) During the breeding season, a high proportion of birds that prey on insects contribute to the provision of potential ecosystem services. In conclusion, the reserve could develop seasonal conservation strategies tailored to the characteristics of bird communities in various seasons, with a specific emphasis on protecting key ecological niche bird species, particularly those exhibiting unique traits and birds that consume insects.